Implementasi manajemen relaksasi progresif untuk penurunan burnout pada karyawan PT. CAT - Lestari, Putri Yuni Indah; Amelasasih, Prianggi (PSYCOMEDIA : Jurnal Psikologi, 2024)
Employee performance and quality have an important influence on the company. In the process of carrying out tasks, employees do not always run smoothly, and problems often arise that can affect performance, one of which is burnout. Burnout can affect the quality of employee performance. The aim of this research was to determine the effect of progressive relaxation management training on burnout at PT CAT. This research uses a quasi-experimental pre- and post test design. The subjects of this research were seven people. The training was carried out over 8 meeting sessions with relaxation material, including the meaning of relaxation, benefits, and relaxation techniques. Statistical test analysis uses the Wilcoxon Signed Rank Test, which is a non-parametric test to analyze the significance of differences between two paired data on an ordinal scale. The results of this research show that there is a significant reduction in burnout levels in PT CAT employees after being given progressive relaxation training